DNA Nanoflowers for Multiplexed Cellular Imaging and Traceable Targeted Drug Delivery1. Issue 23 (17th April 2014) - Hu, Rong; Zhang, Xiaobing; Zhao, Zilong; Zhu, Guizhi; Chen, Tao; Fu, Ting; Tan, Weihong
Abstract We present a facile approach to make aptamer‐conjugated FRET (fluorescent resonance energy transfer) nanoflowers (NFs) through rolling circle replication for multiplexed cellular imaging and traceable targeted drug delivery. The NFs can exhibit multi‐fluorescence emissions by a single‐wavelength excitation as a result of the DNA matrix covalently incorporated with three dye molecules able to perform FRET. Compared with the conventional DNA nanostructure assembly, NF assembly is independent of template sequences, avoiding the otherwise complicated design of DNA building blocks assembled into nanostructures by base‐pairing. The NFs were uniform and exhibited high fluorescence intensity and excellent photostability. Combined with the ability of traceable targeted drug delivery, these colorful DNA NFs provide a novel system for applications in multiplex fluorescent cellular imaging, effective screening of drugs, and therapeutic protocol development.